2021
DOI: 10.34190/ejel.19.3.2296
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting the Auditory Attention of Non-native Speakers in e-Learning Environments

Abstract: : One of the most striking characteristics of e-Learning audiences is their diversity. Native and non-native learners can be expected among such audiences and therefore, when developing e-Learning courses it is important to consider the impact of the language level on learning. Specifically, non-native learners are expected to have a diminished auditory perception compared to native ones and hence reduced attention capabilities that could result in a poorer performance. In this study, we assess the impact of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The quantitative improvements across grammar, vocabulary, reading comprehension, and writing skills all point toward the efficacy of ChatGPT as a learning aid. These tools, i.e., chatbots, play a very important role in improving the auditory attention of non-native speakers in the e-learning environment (Bajaj et al, 2021). Similarly, some of the characteristics of the cognate facilitation effect, according to Casaponsa et al, 2015, could be observed through an improvement in vocabulary and grammar, suggesting language learning technologies that take advantage of linguistic similarities could help facilitate understanding and recall among learners.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative improvements across grammar, vocabulary, reading comprehension, and writing skills all point toward the efficacy of ChatGPT as a learning aid. These tools, i.e., chatbots, play a very important role in improving the auditory attention of non-native speakers in the e-learning environment (Bajaj et al, 2021). Similarly, some of the characteristics of the cognate facilitation effect, according to Casaponsa et al, 2015, could be observed through an improvement in vocabulary and grammar, suggesting language learning technologies that take advantage of linguistic similarities could help facilitate understanding and recall among learners.…”
Section: Discussionmentioning
confidence: 99%
“…Under the umbrella of remote education, e-learning encompasses a wide array of technological applications and learning methodologies, including computer-based learning, internet-driven education, and virtual classrooms (Alkindi et al 2022). Therefore, online e-learning in higher education contexts prioritizes the cultivation of metacognitive, reflective, and collaborative learning, transcending the confines of structured subject-based education to emphasize the value of self-directed, incidental learning that enhances performance (Bajaj et al 2021). A significant body of prior research has demonstrated the myriad advantages of e-learning for students, emphasizing its ability to enhance student focus, flexibility, and communication between professors and students (Chen 2009).…”
Section: Introductionmentioning
confidence: 99%